Cardamine hupingshanensis aqueous extract improves intestinal redox status and gut microbiota in Se‐deficient rats. (1st October 2020) - Cheng, Yuxin; Huang, Yuting; Liu, Kunyuan; Pan, Siyi; Qin, Zhiguo; Wu, Ting; Xu, Xiaoyun
Abstract: BACKGROUND: As an essential trace element for mammalian species, selenium (Se) possesses powerful antioxidant properties and is a potential regulator of intestinal microbiota. However, effects of Cardamine hupingshanensis aqueous extract (CE), rich in Se, on balancing the intestinal redox status and regulating gut microbiota have been neglected. RESULTS: An Se‐deficient rat model was established by feeding a low‐Se diet (LD) for 5 weeks and CE was then supplemented to LD or normal‐Se‐diet (ND) rats. Antioxidant enzyme activities and short‐chain fatty acids (SCFA) concentration were increased by CE in both LD and ND rats. CE improved the intestinal morphology of LD rats impaired by deficient Se. Intestinal microbiota demonstrated various changes; for example, Butyrivibrio was increased in LD rats, while Bacteroides, Christensenellaceae, Clostridiaceae and Blautia were enhanced in ND rats. CONCLUSION: Our findings provide evidence that CE shows potential in improving intestinal redox status and regulating gut microbiota. © 2020 Society of Chemical Industry